Cymbella yangbajainensis sp. nov. (Cymbellaceae, Bacillariophyceae), a new cymbelloid species from Tibet Autonomous Region, China - Feng, Huiyuan; Li, Yanling; Blanco, Saúl; Zhang, Wei (Phytotaxa, 2026)
During a survey of freshwater diatoms in high-altitude streams of the Yarlung Zangbo River Basin, Tibet, China, a new species, Cymbella yangbajainensis sp. nov., was found. Its morphology is described in detail based on observations using light and scanning electron microscope. The new species is characterized by strongly dorsiventral valves with capitate apices, a distinct linear-elliptical central area, and the presence of 5–10 round to oval stigmata of varying sizes, which open at the ends of the central ventral striae. The striae are partly biseriate and irregularly arranged in the central and apical portions. Internally, the areolae are rounded to oblong and occluded by silica plates. Valves are 48.7–64.3 μm long, 11.9–14.5 μm wide, with a length-to-width ratio of 3.8–4.9 (n = 34). The striae density is 8–11 in 10 μm at the valve center, increasing to 10–14 in 10 μm towards the apices; the areolae density is 23–32 in 10 μm. The axial area is narrow and follows the curvature of the valve. Cymbella yangbajainensis is compared with morphologically similar taxa: C. tumida, C. percapitata, C. subtruncata, C. arctissima, C. amplificata, C. cistuliformis, C. jachalensis, and C. menyuanensis. It is distinguished from these species by a combination of features including valve dimensions and outline, stria and areola density, and the number and morphology of stigmata.